2016
DOI: 10.4039/tce.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Records of unsuccessful attack byAnoplophora glabripennis(Coleoptera: Cerambycidae) on broadleaf trees of questionable suitability in Canada

Abstract: Discovery of the non-native Anoplophora glabripennis Motschulsky (Coleoptera: Cerambycidae) in Ontario, Canada, in 2003 led to the implementation of an eradication programme. The plan consisted of removing all infested trees and all trees belonging to a genus considered suitable for complete development of this wood-borer that were found within 400 m of an infested tree; however, many of the trees within that 400 m belonged to genera for which suitability for development of A. glabripennis was questionable or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…7). Upon arrival at a tree, the data collector and specialist undertook the following steps (similar to those listed in Turgeon et al 2016;Fig. 8).…”
Section: Operation Plan and Achievementsmentioning
confidence: 99%
See 4 more Smart Citations
“…7). Upon arrival at a tree, the data collector and specialist undertook the following steps (similar to those listed in Turgeon et al 2016;Fig. 8).…”
Section: Operation Plan and Achievementsmentioning
confidence: 99%
“…To mitigate against the possibility that these genera could be targeted by A. glabripennis in Toronto/Vaughan more frequently than they had been in other outbreaks or in the beetle's native rangeand thus escape detectionthe science subcommittee suggested that a host-confirmation survey of trees from these two categories be undertaken. A host-confirmation survey of more than 3000 trees, all within 400 m of a tree with an A. glabripennis emergence hole, was initiated on 1 April 2004 and lasted three years (Turgeon et al 2016). All that was found were signs of oviposition on a single ash (Fraxinus sp.)…”
Section: Pest Population Monitoringmentioning
confidence: 99%
See 3 more Smart Citations